The Morphological Characters of The Malayan Pit Viper Calloselasma rhodostoma (Kuhl, 1824): on The Cephalic Scalation and Distribution Status in Indonesia - Kadafi, Ahmad Muammar; Hamidy, Amir; Kurniawan, Nia (Graduate School, Universitas Brawijaya, 2018)
The examination on variations of morphological characters among 35 specimens of Calloselasma rhodostoma (Kuhl, 1824) from four different populations in Indonesia has been completed in this study. Univariate and multivariate analyzes allowed us to recognize the clustering of four populations through morphological diagnosis. The results of the average body size (Total Length) showed that the largest male is from Kangean Island (579.33 mm), while the largest female is from Java (841.07 mm). Comparison of meristic analysis represented three clusters from Principal Component Analysis (PCA) which is considered to be independent population. Here we also described three types of cephalic scalation variation that called small accessories scales and their distribution in Indonesia. Keywords: C. rhodostoma, Indonesia, Meristic, Morphometry, Viperidae.